Suicidal ideation and subsequent completed suicide in both psychiatric and non-psychiatric populations: a meta-analysis - Hubers, A. A. M. (Epidemiol Psychiatr Sci, 2016)
AIMS. Several authors claimed that expression of suicidal ideation is one of the most important predictors of completed suicide. However, the strength of the association between suicidal ideation and subsequent completed suicide has not been firmly established in different populations. Furthermore, the absolute suicide risk after expression of suicidal ideation is unknown. In this meta-analysis, we examined whether the expression of suicidal ideation predicted subsequent completed suicide in various populations, including both psychiatric and non-psychiatric populations. METHODS. A meta-analysis of cohort and case–control studies that assessed suicidal ideation as determinant for completed suicide in adults. Two independent reviewers screened 5726 articles for eligibility and extracted data of the 81 included studies. Pooled risk ratios were estimated in a random effects model stratified for different populations. Meta-regression analysis was used to determine suicide risk during the first year of follow-up. RESULTS. The risk for completed suicide was clearly higher in people who had expressed suicidal ideation compared with people who had not, with substantial variation between the different populations: risk ratio ranging from 2.35 (95% confidence interval (CI) 1.43–3.87) in affective disorder populations to 8.00 (95% CI 5.46–11.7) in non-psychiatric populations. In contrast, the suicide risk after expression of suicidal ideation in the first year of follow-up was higher in psychiatric patients (risk 1.40%, 95% CI 0.74–2.64) than in non-psychiatric participants (risk 0.23%, 95% CI 0.10–0.54). Past suicide attempt-adjusted risk ratios were not pooled due to large underreporting. CONCLUSIONS. Assessment of suicidal ideation is of priority in psychiatric patients. Expression of suicidal ideation in psychiatric patients should prompt secondary prevention strategies to reduce their substantial increased risk of suicide.